On Disinformation, Elections and Ethiopian Law - Yilma, Kinfe Micheal (Journal of African law, 2021)
Disinformation has become a formidable challenge to the integrity of electoral processes as well as the internal political stability of many countries. This state of affairs has spurred a wave of new regulatory measures in several countries. From stringent rules governing dissemination of political advertisements via social media platforms to media literacy programmes, the past few years saw the introduction of legislative and non-legislative measures in many jurisdictions. Ethiopia is no exception in introducing measures to address the problem. This article examines Ethiopia's policy responses towards addressing the impact of disinformation on the integrity and credibility of elections. It argues that measures taken thus far in Ethiopia appear to address the impact of disinformation on national security and social harmony. As such, Ethiopia has not taken tailored measures to address the impact of disinformation on its democratic aspirations, particularly in holding free, fair and democratic elections.